Educational Counseling in Efforts to Minimize Drop Out Rates in Situ Udik Village - Lina Septianasari; Alya Kahfi Mirawan; Lestari Wulandari; Mila Fauziah; Sri Maryati (Indonesian Journal of Cultural and Community Development, 2023)
Desa Situ Udik is a village located in Bogor region with average age school has not yet reached 9 years. Even though the location of this village is close to the capital city of Indonesia, some children could not complete their high school due to financial reasons. In this regard, we took the initiative to conduct educational counseling with the aim of increasing public awareness of the important of education to elevate their lives. This event became one of our efforts as educators to minimize the number of dropout rates. The participants of this event are the parents, the children who have dropped-out of schools, and learners aged 4-12 years old. The events were scheduled for 2 days in a row. On the first day we held an education seminar for dropped-out of school children and their parents/guardians. On the second day we held an art performance for early-childhood and young learners in Desa Situ Udik to foster their learning motivation. Highlights: Financial constraints: Some children in Desa Situ Udik cannot complete high school due to financial reasons, hindering their educational progress. Educational awareness: The initiative of conducting educational counseling aims to increase public awareness of the importance of education in improving lives. Two-day event: The event includes an education seminar for dropped-out children and their parents on the first day and an art performance for early childhood and young learners on the second day to foster learning motivation. Keywords: Desa Situ Udik, educational counseling, dropout rates, education seminar, art performance